Management of Inferior Turbinate Hypertrophy: A Comparative Study between Partial Inferior Turbinectomy (PIT) and Submucosal Diathermy (SMD) (Medicine Today, 2025)
Introduction: Symptomatic hypertrophy of the inferior turbinate is a common complaint in ENT outpatient departments. When medical management fails, surgical intervention becomes necessary. Among the various surgical options, partial inferior turbinectomy (PIT) and submucosal diathermy (SMD) are widely used for managing inferior turbinate hypertrophy. Objectives: To compare the clinical outcomes of PIT and SMD in a tertiary care setting. Materials and Methods: This prospective randomized comparative study was conducted at the Department of Otolaryngology and Head-Neck Surgery, Rajshahi Medical College Hospital, from December 2016 to November 2017. Sixty patients (aged 18–60 years) with bilateral inferior turbinate hypertrophy unresponsive to medical treatment were enrolled. After informed consent, they were randomly assigned to two groups: Group A (n=30) underwent PIT, and Group B (n=30) underwent SMD. Postoperative symptoms such as nasal obstruction, pain, bleeding, and crust formation were assessed at 2 days, 2 weeks, and 2 months. Data were analyzed using SPSS-23. Results: There were no significant differences in age, sex, socioeconomic status, or body weight (p>0.05) between groups. Group A showed significantly greater improvement in nasal obstruction at 2 weeks (80.0% vs 53.3%) and 2 months (86.7% vs 63.3%). Mild pain after 2 weeks was more prevalent in Group B (56.7% vs 23.3%). Postoperative bleeding was significantly less in Group B after 2 days (10.0% vs 33.3%), while crust formation was higher in Group A at 2 weeks (73.3% vs 43.3%). Conclusion: PIT was more effective in relieving nasal obstruction, whereas SMD had a better safety profile regarding postoperative bleeding and pain.Medicine Today 2025, Vol.37 (2): 198-203